Recombinant human fibroblast growth factor 7 obtained from stable Chinese hamster ovary cells enhances wound healing - Kim, Young Sik; Lee, Jung Soo; Jeong, Mi Yeong; Jang, Ju Woong; Kim, Moon Suk (Biotechnology Journal, 2024)
Although fibroblast growth factor 7 (FGF7) is known to promote wound healing, its mass production poses several challenges and very few studies have assessed the feasibility of producing FGF7 in cell lines such as Chinese hamster ovary (CHO) cells. Therefore, this study sought to produce recombinant FGF7 in large quantities and evaluate its wound healing effect. To this end, the FGF7 gene was transfected into CHO cells and FGF7 production was optimized. The wound healing efficacy of N-glycosylated FGF7 was evaluated in animals on days 7 and 14 post-treatment using collagen patches (CPs), FGF7-only, and CP with FGF7 (CP+FGF7), whereas an untreated group was used as the control. Wound healing was most effective in the CP+FGF7 group. Particularly, on day 7 post-exposure, the CP+FGF7 and FGF7-only groups exhibited the highest expression of hydroxyproline, fibroblast growth factor, vascular endothelial growth factor, and transforming growth factor. Epidermalization in H&E staining showed the same order of healing as hydroxyproline content. Additionally, the CP+FGF7 and FGF7-only group exhibited more notable blood vessel formation on days 7 and 14. In conclusion, the prepared FGF7 was effective in promoting wound healing and CHO cells can be a reliable platform for the mass production of FGF7.
Keywords: Chinese hamster ovary; Chinese Hamster ovary cells; Fibroblast growth factor; Glycosylated; Human fibroblast; Mass production; N-glycosylated; Patch; Recombinant fibroblast growth factor 7; Wound healing; Animals; CHO Cells; Collagen; Cricetinae; Cricetulus; Fibroblast Growth Factor 7; Humans; Hydroxyproline; Recombinant Proteins; Transfection; Wound Healing; CHO; N-glycosylated; patches; recombinant FGF7; wound healing